PENINGKATAN PENGETAHUAN PRODUKSI, MUTU PRODUK, DAN KEMASAN PADA UMKM KERIPIK RASTI - Sarifah Tullah, Dewi; Puspitasari, Ratih; Abdillah, Fatimah; Julien, Gladys; Febrian, Jan; Lauwsetia, Chessa Auriel (Universitas Mataram, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy, yet they still face limitations, particularly in production, product quality, and packaging. Keripik Rasti MSME as the community service partner encounters similar issues, including limited equipment, inconsistent quality standards, and less informative packaging. This program aims to enhance business owners’ knowledge and skills in production, quality control, and packaging to increase competitiveness. The methods employed included interviews, socialization, training, technical assistance, and evaluation through pre- and post-training questionnaires, with data analyzed using the Paired Sample t-test. The results showed significant improvements in production, product quality, and packaging aspects. Prior to the program, most indicators were in the low–neutral category, while after the program, they increased to high–very high. Tangible changes were observed in the adoption of production machines, quality standards, and the use of aluminum foil packaging with more detailed labels. Statistical tests confirmed these findings with p = 0.000 (<0.05), indicating significant differences before and after the program. Therefore, it can be concluded that the training and mentoring activities successfully equipped Keripik Rasti MSME with practical knowledge and skills in production, product quality, and packaging, thereby strengthening its competitiveness and business sustainability.